(untitled) (Tokyo, 1983)
The present comparative study was attempted with a view to establishing and promoting an exchange of information on nitrogen economy of paddy soil between tropical and temperate regions. It also provided an orpportunity for scientists in Thailand and Japan to cooperatively undertake field and laboratory studies in order to develop information on each process of nitrogen cycle, total nitrogen balance and effect on fertilizer use.
Keywords: Fertilizers,Rice, effect of nitrogen on,Soil science,Cây lúa,Phân bón,Đất cây trồng; Application